The prevalence of sexual dysfunction and erectile dysfunction in men with multiple sclerosis: A systematic review and meta-analysis - V. Shaygannejad; O. Mirmosayyeb; S. Vaheb; N. Nehzat; M. Ghajarzadeh (Neurología (English Edition))
Background: The prevalence of sexual dysfunction (SD) in men with multiple sclerosis (MS) is reported variously in different studies. The most common form of SD in these patients is erectile dysfunction (ED). The goal of this systematic review and meta-analysis is to determine the pooled prevalence of SD and ED in men suffering from MS. Methods: We searched PubMed, Scopus, EMBASE, CINAHL, Web of Science, and gray literature (references of references, and congress abstracts) up to 14th November 2020. Results: We found 3163 studies by primary search, 2246 were included after deletion of duplicates. Finally, 29 studies were included for meta-analysis. A total of 3349 patients were evaluated. The pooled prevalence of SD was 66% (95% CI: 64%–69%). The pooled prevalence of erectile dysfunction was 49% (95% CI: 47%–50%). Conclusion: Sexual dysfunction is a prevalent complication of MS in male patients which should be considered by clinicians. Resumen: Antecedentes: La prevalencia de la disfunción sexual (SD) en hombres con esclerosis múltiple (EM) se informa de forma diversa en diferentes estudios. La forma más común de SD en estos pacientes es la disfunción eréctil (DE). El objetivo de esta revisión sistemática y metanálisis es determinar la prevalencia combinada de SD y DE en hombres que padecen EM. Métodos: Se realizaron búsquedas en PubMed, Scopus, EMBASE, CINAHL, Web of Science y literatura gris (referencias de referencias y resúmenes de congresos) hasta el 14 de noviembre de 2020. Resultados: Encontramos 3163 estudios por búsqueda primaria, 2246 permanecieron después de la eliminación de duplicados. Finalmente, 29 estudios fueron incluidos para metanálisis. Se evaluaron en total 3349 pacientes. La prevalencia combinada de SD fue del 66% (IC del 95%: 64%–69%). La prevalencia combinada de disfunción eréctil fue del 49% (IC del 95%: 47%–50%). Conclusión: La disfunción sexual es una complicación frecuente de la EM en pacientes masculinos que debe ser considerada por los médicos.